Metode Peningkatan Daya Dukung Tanah Lunak - I Gusti Ngurah Nyoman Wismantara; Putu Budiarnaya (Jurnal Ilmiah Telsinas, 2020)
Many sites in Indonesia contain of soft soils which mainly located in farming areas, slopes, alluvials, low level areas. The main problem of soft soils for performing construction work is big settlement which is caused due to low ultimate bearing capacity of soils.These low bearing capacities occurred because of consolidation process proceeded in long time and slowly. To solve this problem the geotechnicians has tried to modify some methods to increase the ultimate bearing capacity of soft soils. There are many methods have been introduced and widely used for increasing bearing capacity. This paper discuss about four methods such as Bamboo Piles Method, Pre Loading Method, Vertical Sand Drainage Method, Geotextile Method.Bamboo Piles Method use bamboo as reinforced soft soils. Pre Loading Method used Pre Loading as the beginning loading. This loading aimed to conduct process of settlement in shortier time. Vertikal Sand Drainage Method required installation of vertical Drainage to clear sands on the soils layer. After draining and pre loading consolidation process was expected would be proceeding in shorter time. Geotextile Method used material of geotextile as tension force to reinforce soft soils so that the ultimate bearing capacity increased. The maximum bearing capacity would be obtained if users installed it as well as soil's layer condition.